2020
DOI: 10.1177/1747021820908538
|View full text |Cite
|
Sign up to set email alerts
|

Double-letter processing in developmental and skilled handwriting production: Evidence from kinematics

Abstract: In this study, we investigated the effects of double-letter processing on handwriting production in beginning and skilled writers of German. One hundred and thirty-seven children from Grades 2 and 3 and 31 adult participants were asked to copy words with double consonants (e.g., “Kanne”) and matched words without double consonants (e.g., “Kante”) from a computer screen onto a pen tablet, while their handwriting was recorded with high spatio-temporal resolution. Handwriting productions were analysed in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…In addition, Gentner et al (1988) found that the keyboard's layout affected how the user transitioned from one keystroke to the next (adjacency and same-finger key repetition, see. also Hess, Mousikou, & Schroeder, 2020).…”
Section: Three-word Combinationmentioning
confidence: 99%
“…In addition, Gentner et al (1988) found that the keyboard's layout affected how the user transitioned from one keystroke to the next (adjacency and same-finger key repetition, see. also Hess, Mousikou, & Schroeder, 2020).…”
Section: Three-word Combinationmentioning
confidence: 99%